Adsorption of Crystal Violet Dye onto Anionic Polyacrylamide-Modified Graphite: Equilibrium, Kinetics, and Mechanism - Haider, Bilal; Ahmad, Shoaib; Hussain, Syed Nadir (ASEAN Journal of Chemical Engineering, 2024)
The textile industry is a major source of wastewater with a high concentration of organic and inorganic chemicals, including dyes. In this study, exfoliated graphite was modified using surfactants Sodium dodecyle sulfate (SDS) and N-cetyl-N,N,N- trimethyl ammonium bromide (CTAB) as well as coagulant anionic polyacrylamide (APAM) to improve the adsorption capacity of pure exfoliated graphite to treat simulated crystal violet (CV) dye. This work also studied the effect of contact time, Dye Concentration, pH and adsorbent loading. Furthermore, adsorption kinetics were investigated by varying contact time and dye concentration. It was observed that modification with surfactants SDS and CTAB did not show appreciable results. However, modification of graphite flakes with APAM resulted in 89.27% removal efficiency compared to unmodified graphite flakes. The graphite flakes were characterized using XRF analysis, BET surface area, and FTIR analysis. UV/Vis-Spectrometer analyzed the concentration of dye solution at a wavelength of 592nm. The availability of active sites and its ability to regenerate the exfoliated graphite made it a potential candidate for the adsorption of CV dye. Moreover, Langmuir and Freundlich adsorption models were applied to investigate dye adsorption behavior. It was observed that the Langmuir model provides the best fit for this system.